2014
DOI: 10.5935/abc.20140110
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Drug-Eluting Stents in the Real World: 8-Year Follow-Up

Abstract: Background:Drug-eluting stents have been used in daily practice since 2002, with the clear advantages of reducing the risk of target vessel revascularization and an impressive reduction in restenosis rate by 50%-70%. However, the occurrence of a late thrombosis can compromise long-term results, particularly if the risks of this event were sustained. In this context, a registry of clinical cases gains special value.Objective:To evaluate the efficacy and safety of drug-eluting stents in the real world.Methods:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…1960s: the macroscopic era of polymeric drug delivery. (1) Norplant is an upper-arm-implantable polymeric drug delivery depot for contraceptive use [active pharmaceutical ingredient (API): progestin levonorgestrel]; (2) Ocusert is a drug-eluting polymeric eye implant for the treatment of glaucoma or ocular hypertension (API: pilocarpine); (3) Progestesert is a T-shaped polymeric IUD for contraceptive use (API: progesterone); (4) Transderm Scop is a polymer-based skin-patch drug delivery system for the treatment of motion sickness (API: scopolamine); (5) OROS is a polymeric capsule system for oral delivery (numerous APIs, including salbutamol, nifedipine, hydromorphone, verapamil, paliperidone, nifedipine); ,, (6) Geomatrix is a polymeric tablet system for oral delivery (API: diclofenac, molsidomine, zileuton, nisoldipine, alfuzosin hydrochloride, ropinirole, paroxetine, levodopa, and benserazide); , (7) Gliadel is an implantable polymeric disk for the treatment of glioblastoma multiforme [API: bis­(2-chloroethyl)­nitrosourea (BCNU)]; , (8) Vicryl is a degradable surgical suture; Taxus is a polymer-coated metal drug-eluting stent for prevention of restenosis (API: antiproliferative drugs such as paclitaxel). , 1980s: the microscopic era of polymeric drug delivery. (10) Lupron Depot is a polymeric microparticle for the treatment of prostate, breast, ovarian and endometrial cancers and also for endometriosis, infertility and benign prostatic hypertrophy (API: leuprolide acetate; a luteinizing hormone releasing hormone (LHRH) agonist); (11) Risperdal Consta is an antipsychotic, PLGA based polymeric microsphere, which is a long-acting injectable approved for the treatment of schizophrenia and the maintenance treatment of Bipolar I Disorder (API: risperidone); , (12) Locteron is a polymeric microparticle for the treatment of hepatitis C (API: interferon-α2b); (13) ReGel is a polymeric drug depot delivery system for the treatment of various diseases (API: small molecules, peptides, and proteins). , 1970s: the nanoscopic era of polymer drug delivery.…”
Section: Evolution Of Controlled-release Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…1960s: the macroscopic era of polymeric drug delivery. (1) Norplant is an upper-arm-implantable polymeric drug delivery depot for contraceptive use [active pharmaceutical ingredient (API): progestin levonorgestrel]; (2) Ocusert is a drug-eluting polymeric eye implant for the treatment of glaucoma or ocular hypertension (API: pilocarpine); (3) Progestesert is a T-shaped polymeric IUD for contraceptive use (API: progesterone); (4) Transderm Scop is a polymer-based skin-patch drug delivery system for the treatment of motion sickness (API: scopolamine); (5) OROS is a polymeric capsule system for oral delivery (numerous APIs, including salbutamol, nifedipine, hydromorphone, verapamil, paliperidone, nifedipine); ,, (6) Geomatrix is a polymeric tablet system for oral delivery (API: diclofenac, molsidomine, zileuton, nisoldipine, alfuzosin hydrochloride, ropinirole, paroxetine, levodopa, and benserazide); , (7) Gliadel is an implantable polymeric disk for the treatment of glioblastoma multiforme [API: bis­(2-chloroethyl)­nitrosourea (BCNU)]; , (8) Vicryl is a degradable surgical suture; Taxus is a polymer-coated metal drug-eluting stent for prevention of restenosis (API: antiproliferative drugs such as paclitaxel). , 1980s: the microscopic era of polymeric drug delivery. (10) Lupron Depot is a polymeric microparticle for the treatment of prostate, breast, ovarian and endometrial cancers and also for endometriosis, infertility and benign prostatic hypertrophy (API: leuprolide acetate; a luteinizing hormone releasing hormone (LHRH) agonist); (11) Risperdal Consta is an antipsychotic, PLGA based polymeric microsphere, which is a long-acting injectable approved for the treatment of schizophrenia and the maintenance treatment of Bipolar I Disorder (API: risperidone); , (12) Locteron is a polymeric microparticle for the treatment of hepatitis C (API: interferon-α2b); (13) ReGel is a polymeric drug depot delivery system for the treatment of various diseases (API: small molecules, peptides, and proteins). , 1970s: the nanoscopic era of polymer drug delivery.…”
Section: Evolution Of Controlled-release Polymersmentioning
confidence: 99%
“…1960s: the macroscopic era of polymeric drug delivery. (1) Norplant is an upper-arm-implantable polymeric drug delivery depot for contraceptive use [active pharmaceutical ingredient (API): progestin levonorgestrel]; 1 (2)Ocusert is a drug-eluting polymeric eye implant for the treatment of glaucoma or ocular hypertension (API: pilocarpine); 2 (3) Progestesert is a T-shaped polymeric IUD for contraceptive use (API: progesterone); 3 (4) Transderm Scop is a polymer-based skin-patch drug delivery system for the treatment of motion sickness (API: scopolamine);26 (5) OROS is a polymeric capsule system for oral delivery (numerous APIs, including salbutamol, nifedipine, hydromorphone, verapamil, paliperidone, nifedipine); 2,27,28 (6) Geomatrix is a polymeric tablet system for oral delivery (API: diclofenac, molsidomine, zileuton, nisoldipine, alfuzosin hydrochloride, ropinirole, paroxetine, levodopa, and benserazide);29,30 (7) Gliadel is an implantable polymeric disk for the treatment of glioblastoma multiforme [API: bis(2-chloroethyl)nitrosourea (BCNU)];31,32 (8) Vicryl is a degradable surgical suture;34 Taxus is a polymer-coated metal drug-eluting stent for prevention of restenosis (API: antiproliferative drugs such as paclitaxel) 35,36. 1980s: the microscopic era of polymeric drug delivery (10).…”
mentioning
confidence: 99%
“…[ 101 ] A link between denudation and thrombosis has been established [ 102 ] and clinical evidence shows that drug‐eluting stents may potentiate late thrombosis due to delayed reendothelialization. [ 103 ] Even more alarming, discontinuation of antiplatelet therapy in patients who have received paclitaxel and sirolimus‐coated stents is associated with an increased risk of late in‐stent thrombosis. [ 22 ] Following several randomized clinical trials [ 20 ] that showed an association between paclitaxel‐coated balloons and stents with an increased risk of late morbidity compared to their uncoated counterparts, the Food and Drug Administration (FDA) released a warning of caution when utilizing such devices.…”
Section: Discussionmentioning
confidence: 99%